THE INFLUENCE OF POLITICAL MARKETING MIX, CELEBRITY ENDORSEMENT, AND BRAND IMAGE ON VOTING DECISION IN THE 2024 JAKARTA GUBERNATORIAL ELECTION - Rico Ruben Haposan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The development of communication technology and more inclusive access to information has driven the transformation of political communication campaigns, which increasingly adapt strategies from the commercial sector. The 2024 Jakarta gubernatorial election, as a national political barometer, provides an important context to examine how marketing concepts such as the marketing mix, celebrity endorsement, and brand image influence the voting decision of urban voters. This study was conducted with the aim of analyzing whether or not there is an influence received by the election decision from the political marketing mix and celebrity support, where the mediating variable is played by brand image. The quantitative research is a method that implemented in this study using a survey of 400 respondents who were eligible voters and registered in the Permanent Voter List (DPT) for the 2024 Jakarta gubernatorial election, selected proportionally based on the population distribution across six administrative cities. PLS-SEM is implemented to analyze the data with SmartPLS software. The findings indicate that voting decisions are significantly affected by the political marketing mix and celebrity endorsement, both directly and through mediating variables played by brand image. A candidate's brand image can be enhanced by an effective political marketing mix and celebrity endorsement strategy, thereby voters' decision to support the candidate in the 2024 Jakarta gubernatorial election can be strengthened.